Mobile agent based publication alerting system - Sahingoz, Ozgur Koray; Sonmez, A. Coskun (SPRINGER-VERLAG BERLIN, 2006)
This paper introduces a distributed publication alerting service which increases the amount of information in notification message while using information hiding principle. It is aimed to design a mobile agent based publication alerting system (MABPAS) which uses mobile agents to dispatch notification information (generally all text information) about produced publication to subscribers. MABPAS combines the advantages of publish/subscribe communication model and mobile agents into a flexible and extensible distributed execution environment.
Keywords: Computer Science